Cardiotoxicity associated with cancer therapy: Pathophysiology and prevention strategies - Rui Adao (2013)
Cardiotoxicity is one of the most significant adverse effects of cancer treatment, and is responsible for considerable morbidity and mortality. Among the effects of chemotherapeutic agents on the cardiovascular system, the most frequent and serious is heart failure with ventricular systolic dysfunction. Other toxic effects include hypertension, thromboembolic disease, pericardial disease, arrhythmias and myocardial ischemia. For several decades, cancer therapy-induced cardiomyopathy was almost exclusively associated with the use of cumulative doses of anthracyclines, which cause permanent damage at the cellular level. However, new therapeutic agents, such as the monoclonal antibody trastuzumab, induce transient reversible myocyte dysfunction which is unrelated to the dose used. Early identification of potential cardiovascular injury, accurate diagnosis of cardiotoxic events and implementation of appropriate monitoring plans are essential in patients with cancer. Close cooperation between cardiologists and oncologists is thus crucial, in order to balance the risks and benefits of cardiotoxic anticancer therapy. In this article we review the various responses to cardiotoxic cancer treatments and their relationship with the main antineoplastic drugs used in clinical practice. In addition, we discuss the main guidelines on detection and monitoring of cardiotoxicity in patients with cancer.